REALITATE ŞI FICŢIUNE – COORDONATE ALE NARAŢIUNII LUI MARIO VARGAS LLOSA / REALITY AND FICTION – COORDINATES OF THE PROSE OF MARIO VARGAS LLOSA - Liliana Danciu (Incursiuni în imaginar)
The human condition within the context of social reality and history, and individual destiny in relation to moral and religious norms imposed at the collective level, are major themes that in Mario Vargas Llosa’s work become sources of intense narrative and interpersonal conflict. According to the Peruvian writer, an individual's happiness is perpetually constrained by the normative aspects of society, whose purpose is to prevent them from fully realizing their inner potential. This limitation leads to discontent, rebellion, and inevitable revolt aimed at overturning power structures. Literature, dreams (reverie), and eroticism represent some surreal dimensions through which individuals can escape and experience the pleasure of complete freedom. Reality and fiction are two coordinates that, within the tangible geography of Latin America and the creative imagination of its writers, cannot be easily distinguished. Since myth, legend, and history are indistinguishable in the human consciousness of referential reality, they are even less separable within the chronotope of fictional imagination. This article explores the intertwining of these spatio-temporal and existential coordinates by analysing several representative narratives by Mario Vargas Llosa, including Eulogy of the Stepmother, The Wanderings of the Reckless Girl, and The War of the End of the World. Although the characters in these novels may come from the realm of ordinary people, they are far from ordinary. Their exceptional destinies are marked by a profound interiority, characterized by fantastical, complex, and obsessive projections; an exacerbated desire to transcend their condition arbitrarily assigned at birth; an impulse to control others; and, conversely, a drive to overthrow externally imposed power or authority. These traits imbue the destinies of Vargas Llosa’s characters with a distinctly tragic dimension.